UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEPGEOMETRI TRANSFORMASI REFLEKSI SISWA KELAS XII-IPA-B SMA KAMPUS TELUKDALAM MELALUI MODEL PEMBELAJARAN DISCOVERYLEARNING BERBANTUAN MEDIA KERTAS MILIMETER - SARUMAHA, ROHPINUS (Institut Pendidikan Tapanuli Selatan, 2018)
The learning process that is dominated by the teacher and that does not involve students in understanding mathematical concepts will make students get difficulties to interpret the concept with their own sentences, moreover in linking each mathematical concept in problem solving. The purpose of this research was to improve the learning process and to improve the ability to understand geometric concepts of reflection transformation of students of Class XII IPA B of SMA Swasta Kampus through discovery learning model assisted by millimeter block media. The type of research used was Classroom Action Research, with 4 (four) stages, namely planning, action, observation and reflection. Based on the results of the research, the students ability in understanding mathematical concepts showed the improvement where the students easily found geometric concepts of reflection transformation with simple experiments and were able to solve mathematical problems through discovery learning model with the average score was 89.5 from the test given in last cycle. Based on that finding, the researcher suggests that discovery learning model can be used as a solution to improve students understanding of the ability of concepts. Teachers should use and design appropriate learning media in teaching certain material so students can easily understand the concepts being studied.